A case report and literature review on tocilizumab-cured acute necrotizing encephalopathy caused by influenza A virus - Huang, YuKun; Zhou, Bin; Hong, ShaoXian; Cai, YaLi (Frontiers in Pediatrics, 2024)
Abstract: Introduction：Acute Necrotizing Encephalopathy (ANE), is a kind of severe Central Nervous System Disease. The commonest pathogen is the influenza virus. The pathogenesis of ANE is bound up to genetic susceptibility and cytokine storm. Interleukin-6 (IL-6) is deemed as the core function in cytokine storm of ANE and that plays a significant role in evaluating the severity of Influenza-Related ANE. Tocilizumab, an IL-6 antagonist, is known to be safe and effective in the treatment of ANE when used early and has an essential role in improving prognosis and preventing disability. Case Report：This case reports a 2 year 10 month old boy who developed ANE after being infected with influenza A virus (H1N1-2019).After treatment with Tocilizumab, the child's consciousness was clear, no convulsions occurred, the movement of limbs was improved, and the lesions of encephalopathy were significantly reduced.Conclusion：The early use of Tocilizumab is safe and effective for the treatment of ANE caused by influenza virus.